Re‐assessment of the climatic controls on the carbon and water fluxes of a boreal aspen forest over 1996–2016: Changing sensitivity to long‐term climatic conditions. (14th May 2022) - Liu, Peng; Barr, Alan G.; Zha, Tianshan; Black, T. Andrew; Jassal, Rachhpal S.; Nesic, Zoran; Helgason, Warren D.; Jia, Xin; Tian, Yun
Abstract: Recent evidence suggests that the relationships between climate and boreal tree growth are generally non‐stationary; however, it remains uncertain whether the relationships between climate and carbon (C) fluxes of boreal forests are stationary or have changed over recent decades. In this study, we used continuous eddy‐covariance and microclimate data over 21 years (1996–2016) from a 100‐year‐old trembling aspen stand in central Saskatchewan, Canada to assess the relationships between climate and ecosystem C and water fluxes. Over the study period, the most striking climatic event was a severe, 3‐year drought (2001–2003). Gross ecosystem production (GEP) showed larger interannual variability than ecosystem respiration ( R e ) over 1996–2016, but R e was the dominant component contributing to the interannual variation in net ecosystem production (NEP) during post‐drought years. The interannual variations in evapotranspiration (ET) and C fluxes were primarily driven by temperature and secondarily by water availability. Two‐factor linear models combining precipitation and temperature performed well in explaining the interannual variation in C and water fluxes ( R 2 > .5). The temperature sensitivities of all three C fluxes (NEP, GEP and R e ) declined over the study period ( p < .05), and, as a result, the phenological controls on annual NEP weakened. The decreasing temperature sensitivity of the C fluxes may reflect changes in forest structure, related to the over‐maturity of the aspen stand at 100 years of age, and exacerbated by high tree mortality following the severe 2001–2003 drought. These results may provide an early warning signal of driver shift or even an abrupt status shift of aspen forest dynamics. They may also imply a universal weakening in the relationship between temperature and GEP as forests become over‐mature, associated with the structural and compositional changes that accompany forest ageing. Abstract : Temperature sensitivities of GEP and Re declined over the study period (p 0.05), which may reflect changes in forest structure, related to the over‐maturity of the aspen stand at 100 ‐years of age, and exacerbated by high tree mortality following the severe 2001‐2003 drought.